Legal Protection for Children Born Out of Wedlock from the Perspective of Islamic Family Law and Positive Law - Zaura Frisila Selen; Amru Syahputra Lubis (Fox Justi : Jurnal Ilmu Hukum, 2025)
Children born out of wedlock often face social discrimination and legal obstacles in obtaining their rights, whether related to status, civil law , or inheritance. This article examines legal protection for illegitimate children from four perspectives: family law, positive law, Islamic law, and customary law, using normative juridical methods and a case study of Constitutional Court Decision No. 46/PUU-VIII/2010. This decision opened up space for recognizing the civil relationship between illegitimate children and their biological fathers, although in practice there are still administrative obstacles and social resistance. Differences in views are also evident in Islamic and customary law, which generally still limit the legal relationship between children and their biological fathers. Therefore, harmonization of the legal system and strengthening of state protection are needed so that the rights of illegitimate children can be guaranteed without discrimination, in the best interests of the child.